Analisis Determinan Inflasi di Indonesia Menggunakan Pendekatan Vector Error Correction Model (VECM) Periode 2005-2025 - Putri Lumbantoruan; Asnidar Asnidar; Ahmad Ridha (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the short-term and long-term effects of the money supply, exchange rates, exports, and foreign exchange reserves on inflation in Indonesia. Previous studies have reported inconsistent findings, creating a research gap that this study addresses by applying the Vector Error Correction Model (VECM) to monthly data from 2005–2025 obtained from Bank Indonesia and Statistics Indonesia. The results show that, in the short run, only past inflation significantly affects current inflation. In the long run, the money supply has a significant negative effect, suggesting that increased liquidity is absorbed by productive economic activities and supported by effective monetary policy. Meanwhile, exchange rates, exports, and foreign exchange reserves have significant positive effects on inflation. These findings provide updated empirical evidence on Indonesia's inflation dynamics using the VECM approach.